CHARACTERISTIC OF RAT DUODENUM STRUCTURAL COMPONENTS IN ADMINISTRATION OF CRYOPRESERVED PLACENTA ALONG WITH ACUTE ASEPTIC PERITONEAL INFLAMMATION - Shepitko, К.V. (World of Medicine and Biology, 2015)
In administration of cryopreserved placenta an increase of the average number of ЕС- and ЕСL-cells was established on day 3-7, enabling more permeability of vascular wall and connective tissue of the proper lamina. The reducing number of Р-cells lowers the secretion of pancreatic juice and gallbladder motility. In simulation of acute aseptic inflammation the number of ЕС-cells was reducing, whereas the number of ЕСL-cells was increasing, which was maximally apparent on day 14-21 day. Restoration of endocrine cells representation was the lowest and on day 30 of observation and not always corresponded the values of intact group.
Keywords: placenta; endocrynocyte; inflammation; duodenal ulcer